Diversity of Corticolous Lichens in Cloud Forest Remnants in La Cortadura, Coatepec, Veracruz, México in Relation to Phorophytes and Habitat Fragmentation - Pérez-Pérez, Rosa Emilia; Castillo-Campos, Gonzalo; Cáceres, Marcela Eugenia da Silva (Cryptogamie. Mycologie (1979), 2015)
In order to make an inventory and learn more about the corticolous lichens diversity on the tree layers of the different environments of the cloud forest (Bosque Mesófilo de Montaña, BMM) in La Cortadura, Veracruz, a transect along the best preserved hill of the forest was delimited, in which 100 m2 squared plots were delineated every 25 m and with different orientations on the slope. Lichen coverage was estimated among trees that had a DBH higher than 20 cm, on the orientation with the greatest lichen coverage. A non-quantitative and opportunistic sampling was done as well, among the same phorophytes. The data were analyzed using the principal component analysis. For each orientation on the hill, a Shannon diversity index was obtained. The species indicator analysis was applied, as well as the circular distribution method. The results indicate that within every 100 m2 square plot, there were 62 individuals on average of the different phorophyte taxa, which host 108 lichen species: 52 (49.5%) correspond to foliose lichens, 47 (44.8%) to crustose lichens, 4 (3.8%) to fruticose lichens and 2 (1.9%) to dimorphic lichen thalli. In the BMM, in spite of being heterogeneous, the genus Quercus predominates, which benefits the lichen community, even though it is subject to changes in the forest structure, the available substratum, and to its capability to disperse.